Post-PRRT scans: which scans to make and what to look for - Else A. Aalbersberg; Daphne M. V. de Vries–Huizing; Margot E. T. Tesselaar; Marcel P. M. Stokkel; Michelle W. J. Versleijen (Cancer Imaging, 2022)
Abstract Aim The aim of this study was to evaluate the clinical utility of SPECT/CT (imaging of uptake in tumor lesions and additional findings) and the additional value of planar imaging in order to simplify clinical imaging protocols and decrease patients burden. Materials and methods One hundred consecutive patients with metastatic neuroendocrine tumor (NET) treated with PRRT were included. Post-therapy imaging was performed 24 h after each PRRT cycle by both whole-body planar imaging and abdominal- and thoracic SPECT/CT. All images were evaluated for (1) the presence of new lesions, (2) discordant lesions between the two acquisitions (planar or SPECT), (3) location of lesions on SPECT (abdominal, thoracic, or both), and (4) additional findings on non-contrast enhanced CT imaging. Results In total 368 PRRT cycles including post-therapy imaging were performed in 100 patients. 45 patients had abdominal disease only, whilst in 55 patients the disease was observed on both abdominal and thoracic SPECT. 16 patients had known bone lesions that were visible only on planar imaging as these were out of range of the SPECT/CT. During PRRT, one patient developed multiple new bone metastases after the second cycle of PRRT, which were visible on both planar and SPECT/CT images. In 11 patients additional findings were found on CT images, the most common and relevant being bowel obstruction, pleural effusion, and ascites. Patients who developed ascites during PRRT appeared to do extremely poor; a post-hoc analysis showed that overall survival was 13.2 months in patients that showed ascites during PRRT at any moment and 37.9 months in patients without ascites (p < 0.001). Conclusion From a clinical point of view, thoracoabdominal SPECT/CT imaging is the preferred method for post-PRRT imaging; planar imaging had no added value over SPECT/CT in this cohort. In patients with abdominal disease only on baseline imaging, SPECT/CT of the abdomen only might be sufficient for imaging during the PRRT course. All accompanying CT images should be reviewed for additional findings, especially ascites, which is suggested to be a poor prognostic factor in patients receiving PRRT.